Marketing Analysis over Start-up Business in Lifestyle (Combining Barbershop and Coffee shop) at PT. Jeeva Work Corporation - Mauritius Kurniawan; Tantri Yanuar Rahmat Syah; Semerdanta Pusaka; Rhian Indradewa (Penerbit Kemala Indonesia, 2020)
The phenomenon of changing the hair style and coffee shop has become a part of our lifestyle. Business opportunities in both sectors are very large. In 2020, the barbershop market share is 52.65% or 74,921 people in the area of West Java, with a population of 142,300 inhabitants. PT. Jeeva Work Corporation is a private company in the Barbershop and coffee shop sector especially for men who are starting to try to be stylish and more aware of their appearance by choosing stylish hairstyles. The company takes advantage of this opportunity by establishing a premium barbershop business, which is provides technology to select hair models in the form of menus with a remodeling application and provides rapid registration technology by developing an online registration application, and equipped with coffee shop facilities under the brand of Jeeva Barber Coffee.